Undergraduate EFL Learners’ Experiences as Anxious Academic Writers: A Mixed Method Study - Arifah, Muflihatus Sururil; Nugraheni, Dyah Ayu; Basya, Dihliza; Sari, Novika Purnama (Inspiring: English Education Journal, 2026)
The primary objective of this study is to investigate the EFL learners’ level of anxiety and experiences as anxious academic writers in essay writing course. Selected by using purposive sampling, five students at sixth semester of English Education Department eagerly participate as respondents. Relying on analysis from Cheng (2004) and Holland (2013), a mixed-method approach with explanatory design is employed by applying two methods of data collection: questionnaire analysis and semi-structured interviews. The findings of the study indicate that moderate anxiety predominates when it comes to composing essays. Furthermore, the five participants depict the experiences being struggling with essay writing anxiety as follows: (1) receiving a poor grade from the instructor; (2) not understanding grammar and structure; (3) discovering rigorous guidelines for academic writing that cause them to write sloppily; (4) worrying about organizing their thoughts to ease the readers; (5) feeling confused, stressed, and frustrated when composing essays; and (6) worrying that the results of their essays become discussion samples and do not meet expectations. The findings confirm hands-on evidence from learners’ experiences as the basic data for course designer to unravel writing anxiety, and for researchers particularly in the demesne of English Language Teaching.